The Rose [videorecording (Blu-Ray)] - Kerby, Bill; Goldman, Bo, 1932-; Midler, Bette; Bates, Alan, 1934-2003; Forrest, Frederic; Primus, Barry, 1938-; McCabe, Sandra; Keith, David, 1954-; Stanton, Harry Dean, 1926-2017; Hare, Will, 1919-1997; Bond, Rudy, 1912-1982; Calfa, Don, 1940-; et al. (Criterion collection, 2015)
Tells about rock-and-roll singer Mary Rose Foster (known as the Rose to her legions of fans), whose romantic relationships and mental health are continuously imperiled by the demands of life on the road.